Association between gender and stoke recurrence in ischemic stroke patients with high-grade carotid artery stenosis. (September 2019) - Chen, Chien-Yu; Weng, Wei-Chieh; Wu, Chia-Lun; Huang, Wen-Yi
Highlights: Association between sex and stroke outcome in ICA stenosis patients is unclear. We investigate the influence of gender differences on ischemic stroke outcomes. We recruit ischemic stroke patients with ICA stenosis and divided by genders. The 5-year mortality rate is not different between males and females. Male gender is associated with increased risk of 5-year ischemic stroke recurrence. Abstract: The association between gender and stroke outcome in patients with high-grade internal carotid artery (ICA) stenosis remains unclear. We investigate gender differences in clinical characteristics and outcomes in ischemic stroke patients with high-grade ICA stenosis. Three-hundred and seventy-two acute ischemic stroke patients with high-grade ICA stenosis were enrolled and followed up for 5 years. Demographic features, vascular risk factors, co-morbidities, and outcomes were compared between male and female genders. Two-hundred and seventy-three (73.4%) patients were males and 99 (26.6%) patients were females. The prevalence of diabetes mellitus and atrial fibrillation was higher in females (P = 0.031 and P = 0.043), whereas the prevalence of smoking was higher in males (P < 0.001). The 5-year mortality rate was not different between males and females (P = 0.437), whereas the 5-year recurrent stroke rate was significantly higher in males (OR, 2.14; 95% CI, 1.22–3.75; P = 0.004). After adjusting for the established clinical predictors of adverse outcomes, the multivariate Cox regression revealed that male gender is a significant predictor of recurrent ischemic stroke (HR, 1.95; 95% CI, 1.19–3.20; P = 0.008). In conclusion, male gender is associated with increased risk of recurrent ischemic stroke in patients with high-grade ICA stenosis during 5-year follow-up. Further prospective trial to assess whether male gender may benefit from more aggressive vascular risk factors control and treatment strategies for stroke prevention is warranted.